2004
DOI: 10.1080/15459620490250026
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Protection Against Mycobacterium tuberculosis: Quantitative Fit Test Outcomes for Five Type N95 Filtering-Facepiece Respirators

Abstract: In preparing to fit test a large workforce, a respirator program manager needs to initially choose respirators that will fit the greatest proportion of employees and achieve the best fits. This article discusses our strategy in selecting respirators from an initial array of seven NIOSH-certified Type N95 filtering-facepiece devices for a respiratory protection program against Mycobacterium tuberculosis (M. tb) aerosol. The seven respirators were screened based on manufacturer-provided fit test data, comfort, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 12 publications
1
64
0
Order By: Relevance
“…(18) One prior investigation found that respirator design (4 flat fold vs. 14 cup -shaped N95 FFRs) was not a significant factor in respirator fit, (18) whereas another study noted one model of a flat fold respirator was associated with both the highest fit factor pass rate and level of comfort when compared to other N95 FFRs. (19) Facial pressure from N95 FFRs is a common complaint among users that limits their wear over extended periods, (7) so if lower pressures equate with equal protection but greater comfort, users may be more inclined to wear N95 FFRs and this could conceivably translate to improved compliance. In addition, it has been reported that flat fold N95 FFRs can be less expensive to manufacture because they do not require molding or multiple manufacturing steps of a cup-shaped respirator, and that they are favored by some wearers because of their portability (e.g., fit easily into a shirt pocket).…”
Section: Discussionmentioning
confidence: 99%
“…(18) One prior investigation found that respirator design (4 flat fold vs. 14 cup -shaped N95 FFRs) was not a significant factor in respirator fit, (18) whereas another study noted one model of a flat fold respirator was associated with both the highest fit factor pass rate and level of comfort when compared to other N95 FFRs. (19) Facial pressure from N95 FFRs is a common complaint among users that limits their wear over extended periods, (7) so if lower pressures equate with equal protection but greater comfort, users may be more inclined to wear N95 FFRs and this could conceivably translate to improved compliance. In addition, it has been reported that flat fold N95 FFRs can be less expensive to manufacture because they do not require molding or multiple manufacturing steps of a cup-shaped respirator, and that they are favored by some wearers because of their portability (e.g., fit easily into a shirt pocket).…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated air exhaust outlets should by located ≥8 m from windows, air intakes and occupied areas, or effectively decontaminated by in-duct ultraviolet germicidal irrigation (UVGI) or high-efficiency particulate air filtration. Upper room UVGI fixtures, professionally designed, installed and maintained, are an effective and sustainable option for limited-resource settings [87–89]. Air recirculation and room air cleaners are not recommended for high M. tuberculosis transmission risk areas.…”
Section: Infection Control Measures For Mdr/xdr-tbmentioning
confidence: 99%
“…Respiratory protection: The efficiency of an N95 respirators is 95%, with a real-world face-seal leakage rate of 0-39% [8,[47][48][49][50]. Adherence ranges between 44% and 97% [51][52][53].…”
Section: 1amentioning
confidence: 99%